A spatially differentiated water pollution policy leads to economic and health inequity - Zhonghui Luo; Lala Ma; Rui Xie; Ran Song (Proceedings of the National Academy of Sciences, 2025)
Disparities in air pollution exposure by socioeconomic status (SES) are well documented. However, there is much less evidence on the inequitable consequences of water pollution and policies affecting water pollution gaps. This study uncovers the distributional impact of China’s 11th Five-Year Plan (2006–2010), which triggered spatially differentiated water pollution abatement for a population of almost 1.3 billion. We document that the policy reduced water pollution overall, targeting areas based on pollution level. Since high pollution areas tend to be wealthier, this policy concentrated firm water pollution abatement and reductions in polluting firm entry in higher-SES areas. While pollution fell, the policy further widened the gap in health and economic outcomes, particularly for those without tap water access: Disparities in risks of tumor, cardiovascular disease, labor supply, and wages increased. Our findings demonstrate that policy-induced changes in water pollution can interact with unequal access to defensive infrastructure to exacerbate SES gaps in outcomes. The analysis also suggests that consideration of heterogeneous pollution vulnerability across the population may affect the overall benefits of a policy.